(untitled) (The International Journal for Scientific Research, 2026)
Andalusia Arabs were well informed with the schools, styles, and trends of Oriental Arab poets. They knew that Oriental poetry represented two schools and trends: the classical school and the modern one. The two schools and trends coexisted together in Andalusia (today’s Spain). They even were sometimes adopted by the same poet. Hence, this study is intended to give a clear picture of the concept of these two schools of poetry as perceived by Andalusia Arabs and it elaborates on Andalusia poets’ assimilation of the two trends. And explaining the reasons for the dominance of the classical school. One of the most important findings of this study is that the early Arab style of poetry recitation was prevalent among Andalusian poets, and that the main motivations for most Andalusian poets to follow this style were: the efforts of rulers, the influence of educators, Eastern music, Eastern poets, the general political climate, and critics. The researcher recommends that scholars continue to explore and discuss this literary critical issue and its research.